Soft magnetic metal powder, magnetic core and magnetic component

The soft magnetic metal powder with a tailored particle size distribution addresses the challenge of achieving improved DC superposition characteristics in magnetic cores, resulting in enhanced magnetic performance.

JP2025058542APending Publication Date: 2025-04-09TDK CORP

Patent Information

Application Number
JP2023168535
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-04-09

AI Technical Summary

Technical Problem

Existing soft magnetic metal powders struggle to produce magnetic cores with improved DC superposition characteristics due to high core losses and difficulties in achieving high density during molding.

Method used

A soft magnetic metal powder with specific particle size distribution characteristics, including a D50 between 3.0 μm and 30.0 μm, and a calculated value of (D95/D50 - D90/D50) / (0.95-0.90) of 20.0 or less, is used to fabricate magnetic cores with enhanced DC superposition characteristics.

Benefits of technology

The use of this soft magnetic metal powder results in magnetic cores with improved DC superposition characteristics, as evidenced by a relative permeability decrease of 10% or less when DC current is applied, indicating better magnetic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025058542000014
    Figure 2025058542000014
  • Figure 2025058542000015
    Figure 2025058542000015
  • Figure 2025058542000001
    Figure 2025058542000001
Patent Text Reader

Abstract

To provide a soft magnetic metal powder capable of manufacturing a magnetic core of which the DC superposition characteristic is improved, a magnetic core of which the DC superposition characteristic is improved, etc.SOLUTION: A soft magnetic metal powder contains soft magnetic metal particles of which the particle size is 5.0 μm or more. In particle size distribution of the soft magnetic metal particle of which the particle size is 5.0 μm or more, when a value of D95 is defined as y95 (μm), a value of D90 is defined as y90 (μm) and a value of D50 is defined as y50 (μm), (y95 / y50-y90 / y50) / (0.95-0.90) is 20.0 or less. A magnetic core contains soft magnetic metal particles of which the Heywood diameter is 5.0 μm or more on any cross section. In particle size distribution of soft magnetic metal particles of which the Heywood diameter is 5.0 μm or more, when the value of D95 is defined as Y95 (μm), the value of D90 is defined as Y90 (μm) and the value of D50 is defined as Y50 (μm), (Y95 / Y50-Y90 / Y50) / (0.95-0.90) is 20.0 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a soft magnetic metal powder, a magnetic core, and a magnetic component. [Background technology]

[0002] Patent Document 1 describes an inductor in which a dust core obtained by compressing metal magnetic powder is integrally molded with a coil portion.

[0003] When metal magnetic powder is used for the dust core, the core loss tends to be large. By using amorphous alloy powder as the metal magnetic powder, the core loss is reduced. However, it becomes difficult to increase the density of the dust core during molding.

[0004] Patent Documents 2 and 3 describe the use of a mixture of crystalline magnetic alloy powder and amorphous magnetic alloy powder.

[0005] Patent Document 4 describes that by using an amorphous soft magnetic powder having a high average practical sphericity, it is possible to provide an inductor or the like having lower loss than before. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2003-309024 A [Patent Document 2] JP 2004-197218 A [Patent Document 3] JP 2004-363466 A [Patent Document 4] Patent No. 5110660 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the exemplary embodiments of the present invention is to provide a soft magnetic metal powder capable of producing a magnetic core with improved DC bias characteristics, and a magnetic core with improved DC bias characteristics, etc. [Means for solving the problem]

[0008] In order to achieve the above object, the soft magnetic metal powder of the exemplary embodiment of the present invention is A soft magnetic metal powder containing soft magnetic metal particles having a particle diameter of 5.0 μm or more, In the particle size distribution of the soft magnetic metal particles having a particle diameter of 5.0 μm or more, the value of D95 is y 95 (μm), D90 value y 90 (μm), D50 value y 50 (μm), (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is less than or equal to 20.0.

[0009] In the particle size distribution of all the soft magnetic metal particles contained in the soft magnetic metal powder, D50 may be 3.0 μm or more and 30.0 μm or less.

[0010] In order to achieve the above object, a magnetic core according to an exemplary embodiment of a first aspect of the present invention is a magnetic core containing the above soft magnetic metal powder.

[0011] In order to achieve the above object, a magnetic core according to an exemplary embodiment of a second aspect of the present invention comprises: A magnetic core containing soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in any cross section, In the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more, the value of D95 is Y 95 (μm), D90 value Y 90 (μm), D50 value Y 50 (μm), (Y 95 / Y 50 -Y 90 / Y 50) / (0.95-0.90) is less than or equal to 20.0.

[0012] The area ratio of the magnetic material in any cross section may be 70% or more and 95% or less.

[0013] The magnetic component of the exemplary embodiment of the present invention includes the magnetic core described above. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is an example of a chart obtained by X-ray crystal structure analysis. [Diagram 2] FIG. 2 is an example of a pattern obtained by profile fitting the chart of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] Below, the soft magnetic metal powder and the magnetic core according to the embodiment of the present invention will be described, but before that, the method for measuring the particle diameter of each particle in the soft magnetic metal particles contained in the soft magnetic metal powder and the method for measuring the particle diameter of each particle in the soft magnetic metal particles contained in the magnetic core will be described. Note that the particle diameter of each particle is the circle area equivalent diameter. Hereinafter, the circle area equivalent diameter may be simply called the circle equivalent diameter.

[0016] There is no particular limit to the method for measuring the particle size of each particle in the soft magnetic metal particles contained in the soft magnetic metal powder. For example, it can be measured by various particle size analysis methods such as laser diffraction. In particular, it may be confirmed using a particle image analyzer, Morphologi G3 (Malvern Panalytical). Morphologi G3 is a device that disperses powder with air, projects the shape of each particle, and evaluates the resulting projection.

[0017] Specifically, the circle-equivalent diameter (particle diameter) of each particle can be obtained from the projected area of ​​each particle. In this embodiment, the circle-equivalent diameters of at least 2000 particles, preferably 20000 particles or more, are measured.

[0018] Morphologi G3 can create and evaluate projection images of many particles at once, making it possible to evaluate the shapes of many particles in a short time. Therefore, it is suitable for evaluating the particle size distribution of soft magnetic metal powder before compaction. It is possible to create projection images of many particles and automatically calculate the particle size of each particle.

[0019] Next, a method for measuring the particle diameter of the soft magnetic metal particles contained in the magnetic core according to this embodiment will be described. First, the magnetic core is cut at an arbitrary location to obtain a cross section. Next, the cross section is observed. There is no particular limit to the method for observing the cross section. For example, an electron microscope (SEM, STEM, TEM, etc.) may be used. There is no particular limit to the observation range and magnification, and it is sufficient to observe the individual cross-sectional shapes of at least 2000 or more soft magnetic metal particles.

[0020] Next, calculate the circle-equivalent diameter (Heywood diameter) of each particle within the observation range. There are no particular limitations on the method for calculating the circle-equivalent diameter. For example, an analysis program or the like may be used. However, when using an analysis program or the like, there is a possibility that parts that are clearly not particles may be recognized as particles. Such parts are appropriately excluded.

[0021] The particle size distribution based on the number of soft magnetic metal powder particles confirmed by Morphologi G3 does not match the particle size distribution based on the number of soft magnetic metal particles in the cross section of the final magnetic core.

[0022] However, there is a correlation between the particle size distribution of the soft magnetic metal powder based on the number of particles confirmed by Morphologi G3 and the particle size distribution of the soft magnetic metal particles based on the number of particles in the cross section of the final magnetic core. Therefore, by confirming the particle size distribution of the soft magnetic metal powder with Morphologi G3, it is possible to predict the particle size distribution of the soft magnetic metal particles in the cross section of the final magnetic core to some extent. In other words, it is easy to control the particle size distribution of the soft magnetic metal particles based on the number of particles in the cross section of the final magnetic core by controlling the particle size distribution and circularity of the soft magnetic metal powder before molding.

[0023] (Soft magnetic metal powder) The soft magnetic metal powder according to this embodiment may have a D50 of 3.0 μm or more and 30.0 μm or less. The above D50 is calculated from the circle-equivalent diameter of all the soft magnetic metal particles contained in the soft magnetic metal powder. D50 is the particle diameter when the cumulative relative frequency based on the number is 50% (0.50).

[0024] Separately, all soft magnetic metal particles having a particle diameter of 5.0 μm or more are picked up from the soft magnetic metal particles contained in the soft magnetic metal powder. The number ratio of soft magnetic metal particles having a particle diameter of 5.0 μm or more in the soft magnetic metal powder according to this embodiment is not particularly limited. For example, it may be 10% or more. If a magnetic body is produced using only the soft magnetic metal powder according to this embodiment, the area occupied by soft magnetic metal particles having a particle diameter of 5.0 μm or more in the cross section of the magnetic body may be 10% or more.

[0025] In the soft magnetic metal powder according to this embodiment, the D95 value in the particle size distribution of the soft magnetic metal particles having a particle diameter of 5.0 μm or more is y 95 (μm), D90 value y 90 (μm), D50 value y 50 (μm), (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is less than or equal to 20.0.

[0026] In the particle size distribution of soft magnetic metal particles, D50 is the particle size when the cumulative relative frequency based on number is 50% (0.50), D90 is the particle size when the cumulative relative frequency based on number is 90% (0.90), and D95 ​​is the particle size when the cumulative relative frequency based on number is 95% (0.95).

[0027] (y 95 / y 50 -y 90 / y 50By using soft magnetic metal powder in which ) / (0.95-0.90) is 20.0 or less, a magnetic core with improved DC bias characteristics can be produced.

[0028] The meaning of the above formula will be explained. A coordinate plane is set with the horizontal axis representing the cumulative relative frequency based on the number of particles and the vertical axis representing the particle diameter standardized by the D50 value. When the coordinate plane is set in this way, the above formula can be considered to represent the gradient from the point representing the particle diameter when the cumulative relative frequency is 0.90 to the point representing the particle diameter when the cumulative relative frequency is 0.95 on the coordinate plane. In other words, the smaller the value represented by the above formula, the smaller the difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95.

[0029] Conventionally, no particular attention has been paid to the part of the particle size distribution of soft magnetic metal powder where the cumulative relative frequency based on the number is greater than 90% (0.90). The present inventors have focused on soft magnetic metal particles with a particle diameter of 5.0 μm or more among soft magnetic metal powders. When a magnetic core is produced using the soft magnetic metal powder, the soft magnetic metal particles with a particle diameter of 5.0 μm or more have a larger volume ratio per particle in the magnetic core than soft magnetic metal particles with a particle diameter of less than 5.0 μm. In other words, the present inventors have focused on soft magnetic metal particles with a relatively large volume ratio per particle in the magnetic core. It has been found that the DC superposition characteristics of the magnetic core are improved when a magnetic core is produced using a soft magnetic metal powder with a particle diameter of 5.0 μm or more that has a small difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95 so as to satisfy the above formula in the particle size distribution of soft magnetic metal particles with a particle diameter of 5.0 μm or more.

[0030] Below, (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is sometimes simply referred to as A1.

[0031] The present inventors speculate that the reason why the DC bias characteristic is improved when A1 is small is as follows.

[0032] The sharper the particle size distribution of the soft magnetic metal particles contained in the magnetic core, the less likely the magnetic core is to be magnetically saturated. In addition, when focusing on the individual soft magnetic metal particles contained in the magnetic core, the soft magnetic metal particles with a larger particle size are more likely to be magnetically saturated than the soft magnetic metal particles with a smaller particle size. This is because the larger the particle size of the soft magnetic metal particles, the easier it is for magnetic flux to pass through the soft magnetic metal particles. Therefore, in order to make magnetic saturation less likely, it is important that the particle size distribution of the soft magnetic metal particles with a larger particle size is sharp. Therefore, it is important to consider the particle size distribution of soft magnetic metal particles with a particle size of 5.0 μm or more. Furthermore, it is thought that among soft magnetic metal particles with a particle size of 5.0 μm or more, particularly large soft magnetic metal particles are more likely to be magnetically saturated.

[0033] Inductors generally have a magnetic core. Inductor standards include the current value at which the inductance drops by 10% from the inductance when no DC current is applied as one of the indicators of the DC bias characteristics of an inductor. Relative permeability may be used instead of inductance.

[0034] Among the soft magnetic metal particles contained in a magnetic core, particularly large soft magnetic metal particles are easily magnetically saturated, and therefore have a dominant effect on the current value when inductance decreases by 10%. Therefore, among the soft magnetic metal particles contained in a magnetic core, the particle size distribution of soft magnetic metal particles with particularly large particle diameters has a dominant effect on the DC bias characteristics of an inductor having the magnetic core.

[0035] In consideration of the above, the present inventors focused on soft magnetic metal particles having a particle diameter of 5.0 μm or more and a cumulative relative frequency of 0.90 to 0.95 in the particle size distribution. It is believed that magnetic saturation can be particularly suppressed when A1 is small, that is, when the particle size distribution of particles having a cumulative relative frequency of 0.90 to 0.95 is sharp. As a result, it is believed that the DC superposition characteristics of an inductor having a magnetic core made using soft magnetic metal particles having a small A1 are improved.

[0036] There is no particular limitation on the composition of the soft magnetic metal powder according to this embodiment. For example, compositions that tend to have an amorphous structure, such as Fe-Co-BP-Si-Cr, Fe-Si-B, Fe-Si-BC, Fe-Si-BC-Cr, Fe-Co-PC, Fe-Co-B, and Fe-Co-B-Si, can be mentioned. In addition, compositions that tend to have a nanocrystalline structure, such as Fe-Si-B-Nb-Cu, Fe-Si-B-Nb-P, Fe-Co-BP-Si, and Fe-Co-BP-Si-Cr, can be mentioned. Furthermore, compositions that tend to have a crystalline structure, such as Fe-Si, Fe, Fe-Ni, Fe-Si-Cr, Fe-Si-Al, Fe-Si-Al-Ni, Fe-Ni-Si-Co, Fe-Co, Fe-Co-V, Fe-Co-Si, and Fe-Co-Si-Al can be mentioned.

[0037] The microstructure of the soft magnetic metal powder according to the present embodiment is not particularly limited, and may be an amorphous structure, a nanocrystalline structure, or a crystalline structure.

[0038] The amorphous structure refers to a structure in which the amorphous ratio X is 85% or more. A structure containing crystals in a range in which the amorphous ratio is 85% or more is included in the amorphous structure. The amorphous structure includes a structure that is mostly amorphous or a heteroamorphous structure. The heteroamorphous structure is a structure in which crystals exist in the amorphous material. In the case of a heteroamorphous structure, the average crystal grain size of the crystals existing in the amorphous material may be 0.1 nm or more and 10 nm or less. The nanocrystal structure is a structure in which the amorphous ratio X is less than 85% and the average crystal grain size of the crystals is 100 nm or less. The average crystal grain size of the crystals in the nanocrystal structure may be 3 nm or more and 50 nm or less. The crystal structure is a structure in which the amorphous ratio X is less than 85% and the average crystal grain size of the crystals is greater than 100 nm. The crystal structure is a structure in which the amorphous ratio X is less than 85% and the average crystal grain size of the crystals is greater than 100 nm.

[0039] The amorphous ratio X can be measured by X-ray crystal structure analysis using XRD, and may be measured by EBSD (crystal orientation analysis) or electron beam diffraction. A method for measuring the amorphous ratio X by XRD will be described below.

[0040] The amorphous ratio X of the soft magnetic metal powder is represented by the following formula (1). X = 100 - (Ic / (Ic + Ia) × 100) ... (1) Ic: Crystalline scattering integrated intensity Ia: Amorphous scattering integrated intensity

[0041] The amorphous ratio X is calculated by performing X-ray crystal structure analysis by XRD on the soft magnetic metal powder, identifying the phase, reading the peaks of crystallized Fe or compounds (Ic: crystalline scattering integrated intensity, Ia: amorphous scattering integrated intensity), determining the crystallization ratio from the peak intensity, and calculating the amorphous ratio X using the above formula (1). The calculation method will be described in more detail below.

[0042] X-ray crystal structure analysis is performed on the soft magnetic metal by XRD to obtain a chart as shown in Fig. 7. This is then profile-fitted using the Lorentz function of the following formula (2) to obtain a crystalline component pattern α , which shows the crystalline scattering integrated intensity as shown in Fig. 8. c , amorphous component pattern α showing amorphous scattering integral intensity a , and the combined pattern α c+a From the crystalline scattering integrated intensity and the amorphous scattering integrated intensity of the obtained pattern, the amorphization rate X is calculated by the above formula (1). The measurement range is the diffraction angle 2θ=30° to 60°, where an amorphous-derived halo can be confirmed. In this range, the error between the integrated intensity actually measured by XRD and the integrated intensity calculated using the Lorentz function is set to within 1%.

[0043]

number

[0044] The soft magnetic metal particles contained in the soft magnetic metal powder may be coated. There is no particular limit to the type of coating, and it can be appropriately selected according to the purpose. Examples of the type of coating include oxide glass, phosphate, and SiO2. Examples of the type of oxide glass include P-Zn-Al-O oxide glass, Bi-Zn-B-Si-O oxide glass, and Ba-Zn-B-Si-Al-O oxide glass. There is no particular limit to the thickness of the coating on each soft magnetic metal particle. For example, it may be 0 nm or more and 200 nm or less. In addition, the average coating thickness on the soft magnetic metal particles contained in the soft magnetic metal powder may be 0 nm or more and 200 nm or less.

[0045] (Magnetic core) By producing a magnetic core using the soft magnetic metal powder according to this embodiment, the DC bias characteristics of the obtained magnetic core can be improved.

[0046] There are no particular limitations on the composition of the soft magnetic metal particles contained in the magnetic core according to this embodiment, and the composition may be the same as that of the soft magnetic metal powder according to this embodiment.

[0047] There is no particular limitation on the microstructure of the soft magnetic metal particles contained in the magnetic core according to this embodiment, and the structure may be amorphous, nanocrystalline, or crystalline.

[0048] The magnetic core according to the present embodiment includes the soft magnetic metal particles contained in the soft magnetic metal powder. It may also include soft magnetic metal particles other than the soft magnetic metal particles contained in the soft magnetic metal powder. For example, it may include soft magnetic metal particles having a smaller average particle size than the soft magnetic metal particles contained in the soft magnetic metal powder. There is no particular restriction on the composition of the soft magnetic metal particles having a smaller average particle size. For example, the soft magnetic metal particles having a smaller average particle size may have a composition of Fe, Fe-Ni, Fe-Si, or Fe-Co.

[0049] In addition, the soft magnetic metal particles having a small average particle size may have the same composition and crystal structure as the soft magnetic metal particles contained in the soft magnetic metal powder. For example, compositions that tend to have an amorphous structure such as Fe-Co-BP-Si-Cr, Fe-Si-B, Fe-Si-BC, Fe-Si-BC-Cr, Fe-Co-PC, Fe-Co-B, and Fe-Co-B-Si may be mentioned. In addition, compositions that tend to have a nanocrystalline structure such as Fe-Si-B-Nb-Cu, Fe-Si-B-Nb-P, Fe-Co-BP-Si, and Fe-Co-BP-Si-Cr may be mentioned. In addition, compositions that tend to have a crystalline structure such as Fe-Si, Fe, Fe-Ni, Fe-Si-Cr, Fe-Si-Al, Fe-Si-Al-Ni, Fe-Ni-Si-Co, Fe-Co, Fe-Co-V, Fe-Co-Si, and Fe-Co-Si-Al may be mentioned.

[0050] Various soft magnetic metal particles may be coated. The type of coating is not particularly limited and can be appropriately selected according to the purpose. Examples of the coating include oxide glass, phosphate, and SiO2. Examples of the oxide glass include P-Zn-Al-O oxide glass, Bi-Zn-B-Si-O oxide glass, and Ba-Zn-B-Si-Al-O oxide glass. In particular, the coating thickness of soft magnetic metal particles having a particle diameter of 5.0 μm or more, which will be described later, may be, for example, 0 nm or more and 200 nm or less. In addition, the average coating thickness of soft magnetic metal particles having a particle diameter of 5.0 μm or more, which will be described later, may be 0 nm or more and 200 nm or less.

[0051] The magnetic core according to the present embodiment may have an area ratio of the magnetic material in any cross section of 70% or more and 95% or less. The magnetic material includes various magnetic materials such as the soft magnetic metal particles contained in the soft magnetic metal powder. The magnetic core according to the present embodiment may also include a resin in addition to the magnetic material. There is no particular restriction on the type and content of the resin. Examples of the type of resin include thermosetting resins such as phenol resin and epoxy resin. The content of the resin in the magnetic core may be 1.0 part by mass or more and 5.0 parts by mass or less, assuming that the total mass of the various magnetic materials is 100 parts by mass.

[0052] In addition to the above magnetic materials and resins, the magnetic core according to this embodiment may contain non-magnetic particles within a range in which the DC bias characteristics are favorably maintained, and may also contain modifiers, preservatives, dispersants, etc.

[0053] The area ratio of soft magnetic metal particles having a particle diameter of 5.0 μm or more to the area of ​​the magnetic body in the cross section of the magnetic core is not particularly limited, and may be, for example, 10% to 100%, or 15% to 100%.

[0054] The composition of the magnetic body in the cross section of the magnetic core can be analyzed using EDS, EPMA, etc. Then, when the magnetic core contains magnetic bodies having multiple types of compositions different from each other, it is possible to identify the type of composition each magnetic body has.

[0055] From the soft magnetic metal particles contained in the magnetic core, all soft magnetic metal particles with a particle diameter (Heywood diameter) of 5.0 μm or more are picked up. Soft magnetic metal particles other than the soft magnetic metal particles contained in the soft magnetic metal powder described above are also picked up as long as they have a particle diameter of 5.0 μm or more.

[0056] In the magnetic core according to the present embodiment, the D95 value in the particle size distribution of the soft magnetic metal particles having a particle diameter of 5.0 μm or more is set to Y 95 (μm), D90 value Y 90 (μm), D50 value Y 50 (μm), (Y95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is less than or equal to 20.0.

[0057] Magnetic core (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) being 20.0 or less, the DC bias characteristics of the magnetic core are improved.

[0058] In the past, no particular attention was paid to the portion of the particle size distribution of the soft magnetic metal particles contained in the magnetic core where the cumulative relative frequency based on the number of particles is greater than 90% (0.90). The present inventors focused on soft magnetic metal particles having a particle diameter of 5.0 μm or more, and set the D95 value to Y 95 (μm), D90 value Y 90 (μm), D50 value Y 50 (μm), (Y 95 / Y 50 -Y 90 / Y 50 It has been found that the DC bias characteristics of a magnetic core having a small difference between the particle size when the cumulative relative frequency is 0.90 and the particle size when the cumulative relative frequency is 0.95, such that ) / (0.95-0.90) is 20.0 or less, is improved.

[0059] Below, (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is sometimes simply referred to as A2.

[0060] The present inventors speculate that the reason why the DC bias characteristics improve when A2 is small is the same as the reason why the DC bias characteristics improve when A1 is small.

[0061] The magnetic core produced by pressure molding the soft magnetic metal powder according to the present embodiment is likely to be the magnetic core according to the present embodiment. If the molding pressure is changed between the magnetic core according to the present embodiment and the conventional magnetic core to make the relative permeability μ equal, a magnetic core with high DC bias characteristics can be obtained. There is no particular limit to the relative permeability μ of the magnetic core.

[0062] Hereinafter, the method for producing the soft magnetic metal powder according to this embodiment will be described.

[0063] Soft magnetic metal powder can be produced by various melting methods. It may be produced by a method of rapidly cooling molten metal (melt). This is because rapid cooling makes it easier to obtain soft magnetic metal powder having an amorphous structure. For example, soft magnetic metal powder can be produced by an atomization method. Hereinafter, a method of obtaining soft magnetic metal powder by gas atomization, which is one type of atomization method, will be described.

[0064] First, the raw materials (pure metals, etc.) of each element constituting the soft magnetic metal powder are prepared and weighed to obtain the desired composition of the soft magnetic metal. Then, the raw materials of each element are melted to prepare a master alloy. There is no particular limitation on the melting method. For example, the raw materials of each element may be melted by high-frequency heating in a chamber with a predetermined degree of vacuum.

[0065] Next, the mother alloy is heated and melted to obtain a molten metal. The temperature of the molten metal may be set in consideration of the melting point of the alloy having the desired composition. For example, it may be set to 1200 to 1600°C.

[0066] When obtaining soft magnetic metal powder by gas atomization, molten metal at 1200 to 1600°C is obtained, and then the molten metal is sprayed into a chamber to produce powder. Specifically, the molten metal is sprayed from a discharge port toward a cooling section in the chamber. At that time, high-pressure gas is sprayed toward the sprayed molten metal. The sprayed molten metal is scattered within the chamber by the spray of high-pressure gas, and is rapidly cooled and solidified by colliding with the cooling section (cooling water) to become soft magnetic metal powder.

[0067] There is no particular limitation on the type of high pressure gas. For example, inert gases such as nitrogen gas, argon gas, and helium gas can be used. Alternatively, reducing gases such as ammonia decomposition gas can be used.

[0068] There is no particular limit to the pressure of the injected high-pressure gas. It may be 2.0 to 10.0 MPa. There is no particular limit to the amount of molten metal injected. It may be 0.5 to 4.0 kg / min. By controlling the ratio of the pressure of the high-pressure gas to the amount of molten metal injected, the particle size of the soft magnetic metal powder, etc., can be adjusted.

[0069] The atomizing device used in the gas atomizing method may be an elliptical water flow atomizing device capable of generating an elliptical spiral cooling water flow.

[0070] The particle size of the obtained soft magnetic metal powder may be adjusted by adjusting the particle size by dry classification or wet classification. Examples of dry classification methods include sieve classification using a dry sieve and air classification using differences in mechanical behavior. In wet classification, classification is performed in liquid using centrifugal force or gravity. Examples of wet classification methods include classification by wet filter filtration and classification by centrifugation.

[0071] In order to obtain the soft magnetic metal powder according to this embodiment, that is, to reduce the difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95, and thereby to reduce A1, two or more different classification methods are sequentially performed. Furthermore, when two or more different classification methods are sequentially performed, the classification points by each classification method may be substantially the same. At least the classification points of the classifications performed last and the classifications performed second to last among the different types of classification are substantially the same.

[0072] The classification point when classifying soft magnetic metal powder refers to the D50 of the soft magnetic metal powder obtained by classification. When two or more different classification methods are performed sequentially, the classification points of each classification method being substantially the same means that the value obtained by dividing the classification point of the later classification by the classification point of the earlier classification is 0.9 or more.

[0073] Conventionally, the sequential use of two or more different classification methods has been considered undesirable due to the increased manufacturing costs. In particular, it was thought that making the classification points by each classification method substantially the same would make the subsequent classification meaningless and would simply increase manufacturing costs.

[0074] However, the inventors have found that even particles with the same particle size are more likely to be removed depending on the classification method. For example, sieve classification is relatively easy to remove needle-like irregularly shaped particles. Air classification is relatively easy to remove flat irregularly shaped particles. Wet classification is relatively easy to remove particles with high specific gravity.

[0075] When two or more different classification methods are carried out in sequence and the classification points of the respective classification methods are substantially the same, the second and subsequent classifications remove almost no particles smaller than D90. As for particles with particle diameters of about D90 or larger, some of the types of particles that are easier to remove than in the first classification are removed. As a result, the difference between the particle diameter when the cumulative relative frequency is 0.90 and the particle diameter when the cumulative relative frequency is 0.95 becomes smaller, and A1 decreases.

[0076] An insulating coating may be formed on the soft magnetic metal powder according to the present embodiment. When forming an insulating coating on the surface of the soft magnetic metal particles contained in the soft magnetic metal powder, the soft magnetic metal powder may be subjected to a coating formation treatment such as heat treatment, phosphate treatment, mechanical alloying, silane coupling treatment, or hydrothermal synthesis.

[0077] The application of the soft magnetic metal powder according to this embodiment is not particularly limited. It can be applied to various magnetic parts. In particular, the soft magnetic metal powder can be suitably used as a material for magnetic cores in magnetic parts such as inductors, transformers, and choke coils.

[0078] The type of the magnetic core according to the present embodiment is not particularly limited. Below, a case where the magnetic core is a powder magnetic core will be described. That is, a method of obtaining the magnetic core by pressure molding will be described.

[0079] The method of manufacturing the magnetic core is not particularly limited. For example, first, the soft magnetic metal powder according to the present embodiment and a resin are kneaded to obtain a resin compound. The resin compound may be a granulated powder. At this time, soft magnetic metal powder other than the soft magnetic metal powder according to the present embodiment and / or non-magnetic powder may be added to the resin compound. In addition, a modifier, a preservative, a dispersant, etc. may be added. Then, the resin compound is filled into a mold, pressure-molded, and the resin is then cured to obtain a magnetic core.

[0080] First, the soft magnetic metal powder is mixed with a resin. By mixing the resin, it becomes easier to obtain a molded body with high strength by molding. There is no particular limit to the type of resin. Examples include phenol resin and epoxy resin. There is also no particular limit to the amount of resin added, but it may be 1.0 part by mass or more and 5.0 parts by mass or less, assuming that the total mass of the various magnetic materials is 100 parts by mass.

[0081] The mixture of the soft magnetic metal powder and the resin is granulated to obtain a granulated powder. There is no particular limitation on the granulation method. For example, granulation may be performed using a stirrer. There is no particular limitation on the particle size of the granulated powder.

[0082] The granulated powder is then compressed to obtain a compact. There is no particular restriction on the compression pressure. For example, a compression pressure of 0.1 t / cm is used. 2 More than 20t / cm 2When using a soft magnetic metal powder produced using an elliptical water jet atomizer, the relative permeability μ can be increased with a smaller molding pressure compared to when a conventional atomizer is used.

[0083] The resin contained in the molded body is then cured to obtain a magnetic core. There is no particular limitation on the curing method, and heat treatment may be performed under conditions that allow the resin used to be cured. By using a soft magnetic metal powder having A1 of 20.0 or less and appropriately controlling the amount of soft magnetic metal powder other than the soft magnetic metal powder according to this embodiment, a magnetic core having A2 of 20.0 or less can be obtained.

[0084] There is no particular limit to the use of the magnetic core, and it can be suitably used, for example, as a magnetic core for an inductor.

[0085] Furthermore, the magnetic core and a magnetic part using the magnetic core can be suitably used in electronic devices.

[0086] In particular, the magnetic core described above can be used in fields where miniaturization and low height are required, since it is relatively easy to improve the DC bias characteristic. For example, the magnetic core can be used in magnetic cores, magnetic components, and electronic devices mounted on DC-DC converters. EXAMPLES

[0087] The present invention will be specifically described below with reference to examples.

[0088] (Experimental Example 1) <Soft magnetic metal powder> The various raw materials were weighed out so as to have a soft magnetic metal composition of 58.1Fe-24.6Co-11.0B-3.0P-3.0Si-1.0Cr in atomic weight ratio, and were melted by high-frequency heating to prepare a master alloy. The weighed out various raw materials were then melted by high-frequency heating in a vacuum chamber to obtain a master alloy.

[0089] The prepared master alloy was heated and melted to a molten state metal at 1200°C to 1600°C, and then soft magnetic metal powder having the alloy composition of each sample was produced by gas atomization. Specifically, when the molten master alloy was discharged from the discharge port toward the cooling section (cooling water) in the chamber, high-pressure gas was sprayed toward the discharged dripping molten metal. The high-pressure gas was argon gas. The dripping molten metal was cooled and solidified by colliding with the cooling section (cooling water), becoming soft magnetic metal powder.

[0090] The conditions for the gas atomization method were a high-pressure gas pressure of 2.0 MPa to 10 MPa, and a molten metal ejection rate of 0.5 kg / min to 4.0 kg / min. Each of the above conditions was appropriately controlled so as to obtain the desired soft magnetic metal powder.

[0091] It was confirmed by ICP analysis that the composition of the master alloy and the composition of the powder for each sample were roughly the same. In addition, X-ray diffraction measurements were performed on each powder to measure the amorphization rate X. When the amorphization rate X was 85% or more, it was determined that the powder had an amorphous structure. When the amorphization rate X was less than 85% and the average crystal grain size was 100 nm or less, it was determined that the powder had a nanocrystalline structure. When the amorphization rate X was less than 85% and the average crystal grain size was greater than 100 nm, it was determined that the powder had a crystalline structure. In Experimental Example 1, it was confirmed that all of the soft magnetic metal powders had an amorphous structure.

[0092] Next, the soft magnetic metal powder was subjected to a coating process using a mechanofusion device (Hosokawa Micron Corporation: AMS-Lab) to form a coating of P-Zn-Al-O-based oxide glass on the surface. The coating thickness was set to 15 nm.

[0093] Next, sieve classification, air classification, and / or wet classification were performed in the order shown in Table 1.

[0094] In the sieve classification, the powder was classified using a dry sieve in air. The classification point was adjusted by changing the powder charge per run, the classification time, and / or the mesh size.

[0095] Air classification was performed using a rotor-rotating classifier. The classification point was adjusted by changing the powder input amount, rotor rotation speed, and / or air flow rate.

[0096] Wet classification was performed by classifying the powder in liquid. A filter type wet classifier was used as the classification device. The classification point was adjusted by changing the filter opening, the magnetic material concentration, and / or the inlet flow rate.

[0097] For the samples shown in Table 1, when classification was performed more than once, the classification points for each classification were substantially the same.

[0098] For the samples shown in Table 2, the classification point in the second classification was set to be smaller than the classification point in the first classification. Specifically, for sample numbers 25 to 27, the powder after classification of sample number 22 was subjected to a second classification. For sample numbers 28 to 30, the powder after classification of sample number 23 was subjected to a second classification. For sample numbers 31 to 33, the powder after classification of sample number 24 was subjected to a second classification.

[0099] The y of each sample of soft magnetic metal powder 50 , y 90 and y 95 First, the projected images of individual particles were observed using a Morphologi G3 (Malvern Panalytical). The shapes of 20,000 powder particles were observed at a magnification of 10x. Specifically, 3cc of powder was dispersed at an air pressure of 1-3 bar, and a projected image was taken using a laser microscope. The equivalent circular area diameter in the projected image of each powder particle was then measured as the particle diameter. From the particle diameter of each powder particle, y 50 , y 90 and y 95 Then, A1 was calculated.

[0100] In each sample of Experimental Example 1, all of the soft magnetic metal particles contained in the soft magnetic metal powder were adjusted so that D50 was about 6 μm in the particle size distribution.

[0101] <Small particle powder> In Experimental Example 1, Fe powder was prepared as the small particle powder, as shown in Tables 1 and 2. The average particle size of the small particles was 1 μm. In Experimental Example 1, the small particles contained in the small particle powder were soft magnetic metal particles of a different type from the large particles contained in the large particle powder.

[0102] <Magnetic core> A toroidal core was produced using the soft magnetic metal powder (large particle powder) and the small particle powder of each sample.

[0103] First, the large particle powder, the small particle powder, and the epoxy resin were kneaded to obtain a resin compound. The total mass of the various magnetic materials was 100 parts by mass, and the content of the epoxy resin was controlled to be 2.5 parts by mass. The compounding ratio of the large particle powder and the small particle powder was set so that the area ratio of the large particles to the small particles, which will be described later, was the value shown in Tables 1 and 2. In other words, the ratio (area of ​​the large particles: area of ​​the small particles) was approximately 80:20.

[0104] The resin compound was filled into a mold and pressurized to obtain a toroidal shaped molded body. The molding pressure was controlled so that the relative permeability μ0 (relative permeability when no DC magnetic field is applied) of the final toroidal core was approximately 30.

[0105] The toroidal-shaped molded body was heated at 180°C for 60 minutes to harden the epoxy resin in the molded body, obtaining a toroidal core. The toroidal core had an outer diameter of 11 mm, an inner diameter of 6.5 mm, and a thickness of 2.5 mm. The number of toroidal cores required for the tests described below was produced.

[0106] The A2 in the cross section of the toroidal core, the area ratio of the magnetic material, and the area ratio of the large particles to the small particles were measured.

[0107] First, the toroidal core was cut at an arbitrary cross section. Next, SEM images were observed at a magnification (100 to 1000 times) that allowed for discrimination of whether each particle in the cross section was a large particle derived from the large particle powder or a small particle derived from the small particle powder. At least 2000 large particles were included in the SEM image. The area ratio of large particles to small particles was calculated. The results are shown in Tables 1 and 2. For particles that were difficult to determine whether they were large or small from the SEM image alone, elemental mapping by EDS or the like was also used to distinguish them.

[0108] The Heywood diameter of each soft magnetic metal particle was measured from the shape of each soft magnetic metal particle by analyzing the SEM image. Mac-View (manufactured by Mountec Co., Ltd.) was used as the software for image analysis. The particle size distribution of soft magnetic metal particles with a Heywood diameter of 5.0 μm or more was calculated from the Heywood diameter of each soft magnetic metal particle. 50 , Y 90 and Y 95 was calculated to calculate A2. It was confirmed that A2 was 20.0 or less in all of the Examples shown below. It was confirmed that A2 was more than 20.0 in all of the Comparative Examples shown below.

[0109] The relative permeability μ0 of the toroidal core of each sample was measured using the following method. First, polyurethane copper wire (UEW wire) was wound around the toroidal core. Then, the inductance of the toroidal core at a frequency of 1 MHz was measured using an LCR meter (Agilent Technologies 4284A) without applying a direct current, and the relative permeability μ0 was calculated from the obtained inductance. The results are shown in Tables 1 and 2.

[0110] Furthermore, Isat was measured to evaluate the DC bias characteristics of the toroidal core of each sample. The greater the DC current applied to the toroidal core of each sample, the lower the relative permeability. When measuring the relative permeability of the toroidal core while applying a DC current, the value of the DC current when the relative permeability dropped by 10% from μ0 was taken as Isat. The results are shown in Tables 1 and 2.

[0111] Furthermore, the Isat of sample number 1, which was the same as sample numbers 2 to 21 and 25 to 33 except that sieve classification was performed only once, was used as the standard, and the ratio of Isat to the Isat of sample number 1 was defined as the Isat ratio. When the Isat ratio was 1.10 or more, it was determined that the DC bias characteristics were good. The results are shown in Tables 1 and 2. The Isat ratio was not calculated for sample numbers 22 to 24.

[0112] [Table 1]

[0113] [Table 2]

[0114] As shown in Table 1, in each example in which two or more classification methods were performed at the same classification point when producing the soft magnetic metal powder, A1 was 20.0 or less. As described above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0115] As shown in Table 1, in each of the comparative examples in which only one type of classification method was performed when producing the soft magnetic metal powder, A1 exceeded 20.0 regardless of the number of classifications. As described above, A2 also exceeded 20.0. As a result, no improvement in the DC bias characteristics was observed.

[0116] As shown in Table 2, in each of the comparative examples in which two different classification methods were used at different classification points when producing the soft magnetic metal powder, A1 exceeded 20.0. As described above, A2 also exceeded 20.0. As a result, no improvement in the DC bias characteristics was observed.

[0117] It was confirmed that the particle size distribution (especially A1) of the soft magnetic metal powder obtained by performing classification multiple times using different classification methods and classification points does not change significantly from the particle size distribution of the soft magnetic metal powder obtained by performing classification once at the smallest classification point.

[0118] (Experimental Example 2) The same conditions as those of sample numbers 1 and 17 were used except that the compounding ratio of the large particle powder and the small particle powder was changed. The Isat ratio of each example was calculated based on the Isat of the comparative example, which was substantially the same except that the sieve classification was performed once. The results are shown in Table 3.

[0119] [Table 3]

[0120] Even if the compounding ratio of the large particle powder and the small particle powder was changed, in each example in which two or more kinds of classification methods were performed at the same classification point when preparing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0121] (Experimental Example 3) By changing the particle size of all the soft magnetic metal particles contained in the soft magnetic metal powder, the D50 in the particle size distribution of all the soft magnetic metal particles contained in the soft magnetic metal powder can be changed, and at the same time, the y 50 , y 90 and y 95 The same conditions as those of sample numbers 1 and 17 were used except that the sieve classification was performed once. The Isat ratio of each example was calculated based on the Isat of the comparative example, which was substantially the same except that the sieve classification was performed once. The results are shown in Table 4.

[0122] [Table 4]

[0123] Even when the particle size of the entire soft magnetic metal particles was changed, in each example in which two or more classification methods were performed at the same classification point when producing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0124] (Experimental Example 4) The same conditions as those of sample numbers 1 and 17 were used except that the coating thickness was changed. The Isat ratio of each example was calculated based on the Isat of the comparative example, which was essentially the same except that sieve classification was performed once. The results are shown in Table 5.

[0125] Although A1 is not described in Table 5, y in all the examples 50 , y 90 and y 95 It was confirmed that A1 was 20.0 or less in all the Examples. 50 , y 90 and y 95 was similar to that of Sample No. 1, and it was confirmed that A1 exceeded 20.0 in all the comparative examples.

[0126] [Table 5]

[0127] Even when the coating thickness was changed, in each example in which two or more types of classification methods were performed at the same classification point when producing large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0128] (Experimental Example 5) The same conditions as those of sample numbers 1 and 17 were used, except that the coating formed on the surface of the soft magnetic metal particles was changed to a coating of Bi-Zn-B-Si-O-based oxide glass or a coating of Ba-Zn-B-Si-Al-O-based oxide glass. The Isat ratio of each example was calculated based on the Isat of the comparative example, which was essentially the same except that sieve classification was performed once. The results are shown in Table 6.

[0129] Although A1 is not described in Table 6, y in all the examples 50 , y 90 and y 95 It was confirmed that A1 was 20.0 or less in all the Examples.50 , y 90 and y 95 was similar to that of Sample No. 1, and it was confirmed that A1 exceeded 20.0 in all the comparative examples.

[0130] [Table 6]

[0131] Even when the type of coating was changed, in each example in which two or more types of classification methods were performed at the same classification point when producing large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0132] (Experimental Example 6) The experiments were carried out under the same conditions as for samples 1 and 17, except that the various raw materials were weighed to obtain the soft magnetic metal compositions of 72.3Fe-18.2Si-9.5B (sample numbers 71 and 72), 81.6Fe-3.4Si-13.4B-1.6C (sample numbers 73 and 74), 72.7Fe-11.6Si-10.8B-2.7C-2.2Cr (sample numbers 75 and 76), 56.0Fe-24.0Co-15.0P-5.0C (sample numbers 77 and 78), 56.0Fe-24.0Co-20.0B (sample numbers 79 and 80), and 56.0Fe-24.0Co-15.0B-5.0Si (sample numbers 81 and 82) in terms of atomic weight ratio. The Isat ratio of each Example was calculated based on the Isat of a Comparative Example, which was substantially the same as the Comparative Example except that the sieve classification was performed once. The results are shown in Table 7. In Experimental Example 6, it was confirmed that all of the soft magnetic metal powders had an amorphous structure.

[0133] Although Table 7 omits the value of μ0, it was confirmed that μ0 was around 30 for all samples.

[0134] [Table 7]

[0135] Even if the composition of the large particles was changed, in each example in which two or more types of classification methods were performed at the same classification point when preparing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0136] (Experimental Example 7) The experiments were carried out under the same conditions as those of sample numbers 1 and 17, except that the various raw materials were weighed out to obtain soft magnetic metal compositions of 73.5Fe-13.5Si-9.0B-3.0Nb-1.0Cu (sample numbers 83 and 84), 79.0Fe-1.0Si-10.0B-7.0Nb-3.0P (sample numbers 85 and 86), 63.2Fe-15.8Co-11.0B-9.0P-1.0Si (sample numbers 87 and 88), and 63.2Fe-15.8Co-10.0B-5.0P-5.0Si-1.0Cr (sample numbers 89 and 90) in terms of atomic weight ratio, and that the soft magnetic metal powder was heat-treated to precipitate nanocrystals with a crystal grain size of 30 nm or less and reduce the amorphization rate X to 10%. Specifically, the heat treatment was performed at 400 to 650°C for 10 to 60 minutes. The Isat ratio of each example was calculated based on the Isat of a comparative example that was essentially the same except that sieve classification was performed once. The results are shown in Table 8. In Experimental Example 7, it was confirmed that all of the soft magnetic metal powders had a structure consisting of nanocrystals.

[0137] Although Table 8 omits the value of μ0, it was confirmed that μ0 was around 30 for all samples.

[0138] [Table 8]

[0139] Even if the composition and microstructure of the large particles were changed, in each example where two or more types of classification methods were performed at the same classification point when preparing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0140] (Experimental Example 8) The atomic weight ratios are 88.0Fe-12.0Si (sample numbers 91 and 92), 55.0Fe-45.0Ni (sample numbers 95 and 96), 89.4Fe-8.6Si-2.0Cr (sample numbers 97 and 98), 73.7Fe-16.4Si-9.9Al (sample numbers 99 and 100), 78.1Fe-11.0Si-10.0Al-0.9Ni (sample numbers 101 and 102), and 49.2Fe-42.0Ni-4.0Si-4.8Co (sample The same conditions as those of sample numbers 1 and 17 were used except that various raw materials were weighed to obtain soft magnetic metal compositions of sample numbers 103 and 104), 50.0Fe-50.0Co (sample numbers 105 and 106), 49.0Fe-49.0Co-2.0V (sample numbers 107 and 108), 83.6Fe-4.4Co-12.0Si (sample numbers 109 and 110), and 66.3Fe-7.4Co-16.4Si-9.9Al (sample numbers 111 and 112). In addition, the soft magnetic metal powders of sample numbers 93 and 94 have compositions that essentially contain only Fe. In sample numbers 93 and 94, large particles and small particles cannot be distinguished by SME or EDS. However, if the large particles and small particles can be distinguished, the soft magnetic metal powder (large particle powder) and the small particle powder were blended so that the area ratio of the large particles to the small particles was approximately 80:20. The Isat ratio of each Example was calculated based on the Isat of a Comparative Example, which was substantially the same as the Comparative Example except that the sieve classification was performed once. The results are shown in Table 9. In Experimental Example 8, it was confirmed that all of the soft magnetic metal powders had a crystalline structure.

[0141] Although Table 9 omits the value of μ0, it was confirmed that μ0 was around 30 for all samples.

[0142] [Table 9]

[0143] Even if the composition and microstructure of the large particles were changed, in each example where two or more types of classification methods were performed at the same classification point when preparing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

[0144] (Experimental Example 9) In Experimental Example 9, the experiment was carried out under the same conditions as Sample No. 17, except that a part of the small particle powder was replaced with a medium particle powder containing medium particles described later. In Sample No. 113, a medium particle powder containing Fe-Si-B-Nb-Cu alloy particles having an average particle size of 5 μm and a structure composed of nanocrystals was used. In Sample No. 114, a medium particle powder containing Fe-Si-B alloy particles having an average particle size of 5 μm and a structure composed of amorphous matter was used. In Sample No. 115, a medium particle powder containing Fe-Si alloy particles having an average particle size of 5 μm and a structure composed of crystals was used. The results are shown in Table 10.

[0145] Since the large particle powder is the same as sample number 17, y 50 , y 90 and y 95 is the same as Sample No. 17, and A1 is 20.0 or less in all Examples.

[0146] [Table 10]

[0147] As can be seen from Table 10, there was no significant change in Isat even when a portion of the small particle powder was replaced with the medium particle powder.

[0148] Furthermore, even if a part of the small particle powder in sample number 1 was replaced with a medium particle powder including medium particles described later, there was no significant change in Isat, provided that the magnetic permeability of the obtained magnetic core was equivalent to that of the magnetic core of sample number 1. As shown in Table 10, sample numbers 113 to 115 had similar magnetic permeability and Isat to sample number 17. Therefore, the Isat ratios of sample numbers 113 to 115 were similar to that of sample number 17.

[0149] In samples 113 to 115, the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in the magnetic core was changed by replacing a part of the small particle powder from sample 17 with a medium particle powder. 50 , Y 90 and Y 95It was confirmed that A2 of samples 113 to 115 was 20.0 or less, similar to A2 of sample 17.

[0150] (Experimental Example 10) In sample number 116, Fe-Ni powder was used as the small particle powder. In sample number 1117, Fe-Si powder was used as the small particle powder. In sample number 118, Fe-Co powder was used as the small particle powder. Other points were the same as in sample number 17. The results are shown in Table 11.

[0151] Since the large particle powder is the same as sample number 17, y 50 , y 90 and y 95 is the same as Sample No. 17, and A1 is 20.0 or less in all Examples.

[0152] [Table 11]

[0153] From Table 11, there was no significant change in Isat even when the composition of the small particle powder was changed. As mentioned above, A2 was also below 20.0.

[0154] Furthermore, even if the composition of the small particle powder in sample number 1 was changed, there was no significant change in Isat, provided that the magnetic permeability of the resulting magnetic core was equivalent to that of the magnetic core of sample number 1. As shown in Table 11, sample numbers 116 to 118 had similar permeability and Isat to sample number 17. Therefore, the Isat ratios of sample numbers 116 to 118 were similar to that of sample number 17.

[0155] (Experimental Example 11) The experiment was carried out under the same conditions as samples 1 and 17, except that the area ratio of the magnetic material in the magnetic core was changed by changing the content of the epoxy resin. The results are shown in Table 12.

[0156] All of the samples in Experimental Examples 1 to 10 had the same amount of resin, and the area ratio of the magnetic material was about 85%.

[0157] [Table 12]

[0158] From Table 12, even if the amount of resin was changed, in each example in which two or more types of classification methods were performed at the same classification point when preparing the large particle powder, A1 was 20.0 or less. As mentioned above, A2 was also 20.0 or less. As a result, the DC bias characteristics were good.

Claims

1. A soft magnetic metal powder containing soft magnetic metal particles having a particle diameter of 5.0 μm or more, In the particle size distribution of the soft magnetic metal particles having a particle diameter of 5.0 μm or more, the value of D95 is y 95 (μm), D90 value is y 90 (μm), the value of D50 is y 50 As (μm), (y 95 / y 50 -y 90 / y 50 ) / (0.95-0.90) is 20.0 or less.

2. 2. The soft magnetic metal powder according to claim 1, wherein in the particle size distribution of all soft magnetic metal particles contained in the soft magnetic metal powder, D50 is 3.0 μm or more and 30.0 μm or less.

3. A magnetic core comprising the soft magnetic metal powder according to claim 1 or 2.

4. A magnetic part comprising the soft magnetic metal powder according to claim 1 or 2.

5. A magnetic core including soft magnetic metal particles having a Heywood diameter of 5.0 μm or more in any cross section, In the particle size distribution of the soft magnetic metal particles having a Heywood diameter of 5.0 μm or more, the value of D95 is Y 95 (μm), D90 value Y 90 (μm), D50 value Y 50 As (μm), (Y 95 / Y 50 -Y 90 / Y 50 ) / (0.95-0.90) is 20.0 or less.

6. 6. The magnetic core according to claim 5, wherein the area ratio of the magnetic material in any cross section is 70% or more and 95% or less.

7. A magnetic component comprising the magnetic core according to claim 5 or 6.

Citation Information

Patent Citations

  • Odakusuino jokasochi

    JP1976010660A

  • Coil encapsulating magnetic component and method of manufacturing the same

    JP2003309024A

  • Composite magnetic material, core using the same, and magnetic element

    JP2004197218A

  • Complex magnetic material and method for manufacturing inductor using the same

    JP2004363466A

Cited By

  • Alloy material, magnetic body, and coil component

    WO2025192709A1